Randomized controlled trial of rectal misoprostal and intramuscular oxytocin in the prevention of PPH - A., Savitha; H., Sarita; Gumma, Kashinath (International Journal of Basic & Clinical Pharmacology, 2017)
Background: PPH accounts for merely 23% of maternal mortality in developing countries. Misoprostol is a uterotonic agent and is a PGE analogue commonly used in management of PPH. Oxytocin is another uterotonic agent which is now been introduced as intramuscularly effective agent to prevent PPH.This study aims to compare rectal misoprostol with intramuscular oxytocin in reducing blood loss in third stage of labor to prevent PPH. Objective of present study is to compare the clinical effect of rectal misoprostol with intramuscular oxytocin in prevention of PPH. Methods: A randomized study was conducted over duration of 3 months, at Department of OBG, BRIMS, Bidar, Karnataka, India. Patients with singleton pregnancy with the history of one previous LSCS and opting for elective LSCS were included in the study. Patients with risk pregnancy, such as pre eclampsia, cardiac disease and asthma or grand multipara were excluded from the study. Immediately after spinal anesthesia rectal misoprostol was given while oxytocin was administered after delivery of the baby. Incidence of PPH and amount of blood loss was observed and compared. Results: The difference in both the groups with regard to mean amount of blood loss, mean duration of the third stage of labor, and mean amount of fall in hemoglobin level was not statistically significant as P value was >0.05. The incidence of PPH and the need for additional oxytocic are slightly more in the misoprostol group. The incidence of shivering and pyrexia was more in the misoprostol group, but not so disturbing so as to lead to disuse of this drug. Conclusions: Oral misoprostol, though not a replacement of parenterally administered oxytocin, can be used safely in all deliveries for the prevention of postpartum hemorrhage.